THE ROLE OF INTERNS IN IMPROVING EMPLOYEE PERFORMANCE EFFICIENCY AT ARIF, WAHYUDI & LUKMAN ACCOUNTING SERVICES - Izzuddin, Habib Nur; Yudhanti, Ashari Lintang (Jurnal Pengabdian Masyarakat Sabangka, 2025)
The internship programme implemented through the Merdeka Belajar Kampus Merdeka (MBKM) policy has proven to be able to bridge the gap between theory and practice in the world of work. This study aims to examine the role of interns in making a real contribution to improving employee performance efficiency at the internship programme implementation site. The research method used is the Service Learning method with a descriptive qualitative approach. Data collection was conducted through interviews, observations, and documentation. All data obtained were then analysed using the Miles & Huberman approach, which includes data reduction, information presentation, and conclusion drawing stages. The results of this study indicate that the presence of interns makes a real contribution to improving work efficiency, speeding up service to clients, and reducing the need for overtime because some of the workload can be transferred to the students.